POLA KEPEMIMPINAN MUSA: MENINGKATKAN KUALITAS PELAYANAN GEREJA DI ERA DIGITAL - Situmorang, Sitor; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2024)
In facing cultural and technological shifts in the digital era, there is a phenomenon where congregations tend to shift focus from service goals which should honor God towards achieving self-satisfaction. This shows a shift in values ​​that influence the practice of church services, which should be in accordance with God's will and which should honor and glorify God. Therefore, a good and proportional leadership pattern is needed, such as the leadership pattern shown by Moses in the Bible. Through these conditions, this research tries to analyze a